2011
DOI: 10.1017/s0033291711002832
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing and interaction skills training for parents to change cannabis use in young adults with recent-onset schizophrenia: a randomized controlled trial

Abstract: Training parents in motivational interviewing and interaction skills is feasible and effective in reducing cannabis use among young adults with recent-onset schizophrenia. However, FMI was not more effective than RFS in increasing patients' general level of functioning and in reducing parents' stress and sense of burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…The LEE is easy to administer and, according to the results of this study, the presence of the informal caregiver is not necessarily needed; administration to the patient may provide accurate and sufficient information. In the future, the expressed emotion of caregivers may be decreased with the use of motivational interviewing and the training of interaction skills to improve their strategies (Smeerdijk et al 2012 ). The number of contact hours with a patient might also be decreased for individual caregivers and/or the number of informal caregivers increased and, in such a manner, the burden on caregivers for the mentally ill be kept to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…The LEE is easy to administer and, according to the results of this study, the presence of the informal caregiver is not necessarily needed; administration to the patient may provide accurate and sufficient information. In the future, the expressed emotion of caregivers may be decreased with the use of motivational interviewing and the training of interaction skills to improve their strategies (Smeerdijk et al 2012 ). The number of contact hours with a patient might also be decreased for individual caregivers and/or the number of informal caregivers increased and, in such a manner, the burden on caregivers for the mentally ill be kept to a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…After the psycho-education, the parents received either FMI or RFS, which was scheduled every other week across a 6-month period. The content of the interventions has been described in detail elsewhere (Smeerdijk et al 2009, 2012). Here we provide a brief synopsis.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we developed a family-based intervention for parents of young adults with recent-onset schizophrenia and co-occurring cannabis use; it involved training parents in interaction and motivational interviewing skills. In a RCT we demonstrated that this training, called Family Motivational Intervention (FMI), was significantly more effective than routine family support (RFS) in reducing quantity and frequency of patients’ cannabis use for at least 3 months after completion of the training (Smeerdijk et al 2012). The current study is an evaluation of the effectiveness of FMI at 15 months after the training had ended.…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant decrease in self-reported number of days using cannabis, total grams used, and craving of cannabis observed between assessments at 3 months pre-treatment and 3 months post-treatment. However, there was no significant between-group difference in the proportion of negative urine tests at follow-up [38].…”
Section: Psychosocial Interventionsmentioning
confidence: 69%